THE EFFECT OF FINANCIAL RATIO ON FINANCIAL DISTRESS IN MINING COMPANIES - Nurcahyono Nurcahyono; Putri Adelia; Lany Christanty; Wawan Sadtyo Nugroho (Universitas Muhammadiyah Semarang, 2023)
Empirically this study examines the factors that cause companies to experience financial distress. Financial distress is a phenomenon companies face, especially during a pandemic—detecting financial distress using ratios that describe profitability, use of debt and company activities. The focus of this research is mining companies in Indonesia. The unit of analysis in this research is 18 companies with 72 observations. The data analysis method used is multiple linear regression using the Zmijweski proxy to measure the company's level of financial distress. The research results show that many companies experienced financial distress during the pandemic. Companies with high profitability during a pandemic can prevent the company from going bankrupt. Increased liquidity in mining companies will deter companies from financial distress. Conversely, the higher the debt ratio under conditions of uncertainty, the faster the company will go bankrupt. Finally, the activity ratio cannot predict financial distress, especially in mining companies